1982
DOI: 10.1042/cs0620083
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Free Amino Acids in Undernourished Patients with or without Sepsis

Abstract: 1. Thigh muscle samples for analysis were obtained from 35 control subjects and 12 severely ill patients, of whom five had disease-induced undernutrition and seven had associated sepsis. An improvement in the Bergström technique for analysing muscle needle biopsy samples was used. 2. Muscle water, chloride and DNA were increased in both groups of ill patients, indicating an increase in the extracellular component and loss of muscle protein. 3. Falls in the concentrations of glutamine, glutamate, arginine, hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

1983
1983
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(16 citation statements)
references
References 0 publications
2
12
0
2
Order By: Relevance
“…This finding was described in the early description of this devascularized porcine model of acute liver failure, wherein they also found that the concentrations of citrulline and ornithine were increased (24). In septic patients, low arginine levels (16,25) have also been observed, which is associated with poor outcome. Arginine clearance was found to progressively increase over the duration of the study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was described in the early description of this devascularized porcine model of acute liver failure, wherein they also found that the concentrations of citrulline and ornithine were increased (24). In septic patients, low arginine levels (16,25) have also been observed, which is associated with poor outcome. Arginine clearance was found to progressively increase over the duration of the study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine, the precursor of NO, is a nonessential amino acid for healthy adults but is essential for wound healing, protein anabolism, and immunity after injury [11]. Many studies have indicated that arginine is deficient in sepsis, particularly in patients who died of septic shock [12], and cNOS starts to produce superoxide (O 2 Ϫ ) when arginine concentration is low [13]. Peroxynitrite (ONOO Ϫ ) generated by reaction of NO with O 2…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have proposed that sepsis might be an ARGdeficient state [73]. In both animals and humans with sepsis, plasma ARG concentrations were found to be significantly decreased [50,[74][75][76], suggesting that endogenous synthesis and supply from dietary intake are unable to keep up with the increased demand. In infection body protein breakdown is increased [74] to make more ARG available for nitric oxide synthesis.…”
Section: Arginine Metabolism In Sepsismentioning
confidence: 99%